MTS pilot tone tracking for "wow" distortion determination - Piotr PASTUSZAK (Archives of Acoustics)
New algorithm for the wow distortion characteristic determination using the Multichannel Television Sound (MTS) pilot tone tracking is introduced. By observing variations of the pilot frequency, the depth of the parasitic modulation can be estimated. MTS is an audio coding system proposed by the National Television Standards Committee (NTSC), thus the algorithm is applicable only to NTSC TV standard-based recordings. It is based on the high-frequency bias tracking algorithm and further modified to minimize the influence of acoustic-band audio signals which may interfere with the 15.734 kHz MTS pilot tone.